The genus Calligaster de Saussure (Hymenoptera: Vespidae: Zethinae) in the Philippine Islands - Selis, Marco; Femia, Arturo (Zootaxa, 2022)
The Philippine species of the genus Calligaster de Saussure, 1852 are reviewed. Two species are recorded: C. ilocana Selis, sp. nov. and C. williamsi Bequaert, 1940. Calligaster zetteli Gusenleitner, 2006 is recognized as a synonym of Pseudozumia gracilis van der Vecht, 1963 syn. nov. New distributional records and a key to species are provided.